The Role of Consistent Context in Rapid Movement Planning: Suboptimal Endpoint Adjustment to Changing Rewards. Issue 6 (2nd November 2017) - Neyedli, Heather F.; LeBlanc, Kevin A.
ABSTRACT: The authors' purpose was to determine if participants adjusted their endpoint during a rapid aiming task in the context of changing rewards and whether participants needed consistent feedback to do so. Participants aimed to a target that was overlapped by a penalty region. Participants gained points for hitting the target but lost points for hitting the penalty region. The reward value associated with target contact either changed trial to trial, reducing consistent feedback (variable condition) or changed between blocks of trials (blocked condition) with the repetition of reward value within a block increasing the consistency of feedback. Participants adjusted their endpoints with changing reward value in the blocked but not variable condition indicating consistent feedback is needed to adjust endpoint to changing rewards.